TF-test Coccidia: New cryptosporidium oocysts diagnostic tool and its applications - Inácio, Sandra Valéria [UNESP]; Gomes, Jancarlo Ferreira; Suzuki, Celso Tetsuo Nagase; Falcão, Alexandre Xavier; Coelho, Natália Marinho Dourado [UNESP]; Fukumori, Felipe Yoshio [UNESP]; Guimarães, Renata Mugarte [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2017)
The protozoan genus Criptosporidium is worldwide distributed and is known as an important pathogen.These zoonotic parasites can cause gastric and enteric infections in a long range of vertebrate hosts. To carry out this type of diagnosis, a number of laboratory technical procedures are employed, which basically consist of conventional and commercial kits techniques, which enable the identification of cysts, oocysts, trophozoites and protozoa spores, and as well as eggs and larvae of helminths. However, public and private clinical laboratories that use these technical procedures demonstrate insufficient performance, according to data reported in the literature. Unlike other conventional techniques and commercial kits, the TF-Test or Three Fecal Test technique has been outstanding in recent years with high efficiency in the laboratory diagnosis of human and animal gastrointestinal parasites.
Keywords: Cryptosporidiosis; Protocol; Three fecal test